Preparation of (+)- and (−)- B-phenyl- and B-(4-chlorophenyl)-y-butyrolactones: Key Intermediates in the Synthesis of B-phenyl-GABA and Baclofen. - Jazmín Gómez-Gutiérrez (Journal of the Mexican Chemical Society, 2015)
Thepreparationofβ-phenyl-andβ-(4-chlorophenyl)-γ-bu-tyrolactones( ± )-3and( ± )-4andtheirresolutiontothecorrespond-ing(+)-(S)-3, (−)-(R)-3and(+)-(S)-4, (−)-(R)-4throughformation,flashcolumnchromatographyseparationandsubsequenthydrolysisofdiastereoisomeric4-hydroxybutyramides(2’R,3S)-5,(2’R,3R)-5,(2’R,3S)-6and(2’R,3R)-6isdescribed.Theabsoluteconfigurationassignmentofenantiopure3and4wassupportedbyX-raycrystal-lographicstructuresof(2’R,3R)-5,(2’R,3S)-6and(2’R,3R)-6